Theconcept Of Multiculturalimse In Major Religions In Indonesia - Sukardiman (International Journal of Sociology of Religion, 2024)
Indonesia is known as a plural and multicultural country in all aspects of culture, race, ethnicity, language and religion. So that Multiculturalism can provide an understanding of how to behave in the midst of diversity. Misunderstanding will result in potential conflict, especially that which often occurs between religious communities, so understanding the concept of multiculturalism in all religions is very important. (1) Islam, sees diversity as a necessity from God, because humans were created into tribes, nations, and many religions to get to know each other or learn from each other. (2) Christian, many Bible verses talk about multiculturalism related to compassion between fellow human beings, for example Psalm 133, Galatians 3:28, Matthew: 22:37-40. (3) Catholic, one history explains how in the Second Vatican Council, the Church opened itself to the potential for truth in other religions, so that inclusivity became the key to dialogue with other religions, (4) Hinduism is the same, many of their holy texts explain the importance of maintaining peace in the midst of diversity, for example Arthavaveda III. 8.5 and Artahavaveda III. 30.4. there is also the concept of Ahimsa, Vasudeva Kutumbhakam, Tri Kaya Parisudha, Tri Hita Karana, Satyam Siwam Sundaram, catur paramita. (5) Buddhism is the same as other religions, the greatest enemy is not other groups, but oneself is the greatest enemy in creating peace on earth, (6) Confucianism also teaches about wisdom in behaving towards other religions. The application of multicultural values ​​from all religions certainly needs to be implemented to face challenges in the midst of a multicultural society, such as attitudes of intolerance, misinterpretation or using religion as a tool to destroy other groups by providing multicultural education in the world of education and based on religious figures in each religion.